2004
DOI: 10.1007/bf02829852
|View full text |Cite
|
Sign up to set email alerts
|

Geometry of good sets inn-fold Cartesian product

Abstract: We propose here a multidimensional generalisation of the notion of link introduced in our previous papers and we discuss some consequences for simplicial measures and sums of function algebras.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…In p. 190 of [4], the question whether full components are the same as related components for n ≥ 3, is raised. Theorem 1 of [2] answers the question partially, where it is proved that a full set with finitely many related components is itself related.…”
Section: Example Of a Full Set Which Is Not Relatedmentioning
confidence: 99%
See 3 more Smart Citations
“…In p. 190 of [4], the question whether full components are the same as related components for n ≥ 3, is raised. Theorem 1 of [2] answers the question partially, where it is proved that a full set with finitely many related components is itself related.…”
Section: Example Of a Full Set Which Is Not Relatedmentioning
confidence: 99%
“…Let S be a related set in n-fold cartesian product X 1 × X 2 × · · · × X n . Given two points x, y ∈ S the smallest related subset of S containing x and y is called the geodesic between x and y ( [4], p. 190). In [5], it is shown that if there is an upper bound for lengths of geodesics in S, then the solutions u 1 , .…”
Section: A Set With Unbounded Geodesic Length Which Has Bounded Solutmentioning
confidence: 99%
See 2 more Smart Citations
“…Many papers followed, e.g. [5], [6], [12], [14], [17], [22], [23], [25], [27], and [28] among others, giving different kinds of characterizations in the finite or countable case and going from functional analysis to combinatorics. In particular, Denny [12] extended to the countable case Birkhoff's result about absence of cycles in the support of extremal measures.…”
mentioning
confidence: 99%